Taxonomy and Phylogeny of Two Spirotrichean Ciliates (Alveolata, Protista, and Ciliophora) From a Plateau Saline–Alkaline Lake in Tibet, China, Including Description of a New Species - Kouser, Farzana; Song, Wenya; Jiang, Limin; Zhuang, Wenbao; Wang, Congcong; Wu, Tong; Hu, Xiaozhong (Frontiers in Marine Science, 2022)
Few researches concern ciliates from “extreme” environments such as plateau salt lakes, nevertheless, such faunistic survey is of great significance for understanding the diversity and biogeography of these microeukaryotes. Here, two ciliates, viz., Hemiurosomoida tibetensis sp. nov. and Euplotes euryhalinus Valbonesi & Luporini, 1990, isolated from Kyêbxang Co, a Tibet Plateau saline alkaline lake, China, were investigated based on observations of live and silver-stained specimens as well analyses of 18S rDNA sequences. The new species can be characterized by having a size of 60–95 × 20–40 μm in vivo, an elongate elliptical body, colorless cortical granules mainly grouped around cirri and dorsal bristles, about 21 adoral membranelles, 20 cirri on each marginal row, and two macronuclear nodules and two micronuclei. Chinese population of E. euryhalinus corresponds well with its original isolates. Phylogenetic analyses reveal that Hemiurosomoida is non-monophyletic, and H. tibetensis sp. nov. has a closer relationship with H. longa within this genus, and Euplotes euryhalinus presents a wide geographic distribution. The present study first reveals the ciliature, morphogenesis and rRNA gene sequence data for H. tibetensis sp. nov., and Chinese population of E. euryhalinus, which thus increases our knowledge about diversity of ciliates at high altitude.